Evaluation of 40 rhytidoplasties performed at the Federal Hospital of Andaraí to compare two different techniques: cervicofacial SMAS-plasty according to vector suturing and the sub-SMAS flap approach - Diego Vigna Carneiro (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Rhytidectomy has become one of the most performed aesthetic surgeries in the world. Some surgeons prefer a more conservative approach, and others maintain that aggressive interventions are required to obtain results that are more durable and effective. This study aimed to compare the results of 40 rhytidectomies performed using either of two techniques, namely superficial musculoaponeurotic system (SMAS)-plasty according to vector suturing and the sub-SMAS flap approach, at the Federal Hospital of Andaraí over 22 months. METHODS: This is a descriptive study that included 20 patients who underwent SMAS-plasty and 20 patients who received a sub-SMAS flap. An assessor identified some variables in specific regions of the face from an aesthetic point of view, and he rated improvements based on photographs obtained before and 6 months after operation. The data collected allowed to quantify complications of both techniques separately. RESULTS: From an aesthetic point of view, the two techniques showed similar results in terms of facial rejuvenation, improvement of cervical flaccidity, and definition of face/neck transition. The flap provided better results regarding the attenuation in the nasogenian sulcus. A case of hematoma occurred in each technique. Nerve injury occurred in the SMAS-plasty group. However, neither facial nerve injury nor infection occurred in both groups . Edema for >3 months was more prevalent in the sub-SMAS flap group. CONCLUSIONS: The two methods have advantages and disadvantages, and the best result depended on the degree of aging of the facial skeleton, the loss of supporting tissues in critical areas such as the malar region and next to the labiomandibular fold, the preoperative characteristic of the skin, and the surgeon's experience in the technique.